Skeletal Muscle Change During Neoadjuvant Therapy and Its Impact on Prognosis in Patients With Gastrointestinal Cancers: A Systematic Review and Meta-Analysis - Xu, Xin-Yi; Jiang, Xiao-Man; Xu, Qin; Xu, Hao; Luo, Jin-Hua; Yao, Cui; Ding, Ling-Yu; Zhu, Shu-Qin (Frontiers in Oncology, 2022)
Background: Gastrointestinal cancers are the most common malignant tumors worldwide. As the improvement of survival by surgical resection alone for cancers is close to the bottleneck, recently neoadjuvant therapy has been emphasized and applied in the treatment. Despite the advantage on improving the prognosis, some studies have reported neoadjuvant therapy could reduce skeletal muscle and therefore affect postoperative outcomes. However, the conclusions are still controversial. Methods: PubMed, CINAHL, Embase, and Cochrane Library were searched from inception to 2nd September 2021. The inclusion criteria were observational studies of individuals aged ≥18 years who underwent neoadjuvant therapy with gastrointestinal cancers and were assessed skeletal muscle mass before and after neoadjuvant therapy, published in English, with sufficient data on skeletal muscle change or the association with clinical outcomes. Meta-analysis was conducted by using the STATA 12.0 package when more than two studies reported the same outcome. Results: A total of 268 articles were identified, and 19 studies (1954 patients) were included in the review. The fixed effects model showed that the risk of sarcopenia increased 22% after receiving neoadjuvant therapy (HR=1.22, 95% CI 1.14, 1.31, Z=4.286, P＜0.001). In the random effects model, neoadjuvant therapy was associated with skeletal muscle loss, with a standardized mean difference of -0.20 (95% CI -0.31, -0.09, Z=3.49, P<0.001) and a significant heterogeneity (I2=62.2%, P<0.001). Multiple meta regression indicated that population, neoadjuvant therapy type and measuring tool were the potential sources of heterogeneity. The funnel plot revealed that there was no high publication bias in these studies (Begg’s test, P=0.544) and the sensitivity analysis showed stable results when separately excluding studies. For the postoperative outcomes, the results revealed that muscle loss during neoadjuvant therapy was significantly related to overall survival (HR=2,08, 95% CI =1.47, 2.95, Z=4.12, P<0.001, I2=0.0%), but not related to disease-free survival and other short-term outcomes. Conclusions: This systematic review and meta-analysis revealed that skeletal muscle decreased significantly during neoadjuvant therapy in patients with gastrointestinal cancers, and skeletal muscle loss was strongly associated with worse overall survival. More high-quality studies are needed to update and valid these conclusions in a more specific or stratified way.